A retrospective comparative audit, investigating the glycaemic control implemented in two Intensive Care Units - Tomlinson, Victoria (2011)
Background: Critically ill patients can experience stress-induced hyperglycaemia. Glycaemic control therapy is administered to control patients’ blood glycaemic levels and reduce the incidence of infection, myocardial infarctions and organ failure. However, there are many factors influencing the effectiveness of glycaemic control and contradicting literature. Therefore, there is a need for an audit of current practice.